THE ROLE OF TEACHERS IN IMPROVING THE QUALITY OF EDUCATION FOR STUDENTS WITH DISABILITIES: A LITERATURE REVIEW - Syafwatul Putria Hidayatullah; Mujahiddin (International Journal of Teaching and Learning, 2026)
This article examines the crucial role of teachers in improving the quality of education for students with disabilities. The main focus is on the methods applied by teachers to create learning environments that are inclusive and responsive to students' individual needs. The study identifies that teachers' expertise in designing adaptive learning strategies, as well as the use of assistive technology, are key factors in facilitating effective learning. In addition, the study highlights the importance of collaboration between teachers, families and other professionals to build a comprehensive and sustainable education plan. Thus, the proactive role of teachers contributes not only to the academic development but also to the social and emotional progress of students with disabilities, enabling them to reach their full potential in a supportive and inclusive environment.